Editorial - Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2019)
This final 2019 issue of Studies in Second Language Learning and Teaching brings together six original empirical studies and two book reviews. In the first paper, Marco Octavio Cancino Avila reports the results of a study that investigated the learning opportunities arising in classroom interactions, placing special emphasis on the contribution of teachers’ and learners’ overlapped turns. Using conversational analysis, he analyzed extracts from six classes taught by three teachers to adult learners of English as a foreign language in Chile. He found that teachers’ skill in appropriately handling learners’ turns that overlapped or directly followed their own had a positive impact on participation and language learning as long as learners were given adequate interactional space (Sert, 2015). The second contribution by Reza Shirani also focuses upon classroom interaction, with the caveat that the main concern is with the effectiveness of different types of corrective feedback (CF). The study explored the relationship between the level of explicitness of input-providing (i.e., recasts) and output-promoting (i.e., prompts) CF moves, and the occurrence of uptake and repair in a foreign language context in Iran. Using the model of error treatment proposed by Lyster and Ranta (1997) to analyze transcripts of 36 hours of classroom interactions in three intact classes, the researcher found that prompts tended to be used more frequently than recasts, which stands in contrast to previous findings, but at the same time produced evidence that greater salience of CF is a crucial factor for the occurrence of self-correction, which is in line with prior research.